Genome analysis screening virulence genes for the altered pathogenicity of Riemerella anatipestifer in hens - Lv, Junfeng; Chen, Hui; Ma, Xiuli; Cong, Yang; Song, Xiaofei; Li, Yufeng; Gao, Yuehua; Qin, Zhuoming (Frontiers in Microbiology, 2025)
BackgroundIn recent years, Riemerella anatipestifer infection in chickens has markedly increased, resulting in substantial economic losses to the poultry industry. The present study was designed to assess the pathogenicity of R. anatipestifer in laying hens and to elucidate the molecular mechanisms underlying its altered virulence.MethodsRiemerella anatipestifer strains were isolated from laying hens presenting with oviduct obstruction and diminished egg production. Animal challenge experiments were conducted to evaluate the pathogenic potential of these hen-isolated strains. Genomic DNA sequences were subjected to comparative analysis to identify virulence genes differential between newly hen-derived and previous strains.ResultsThree serotypes, 1, 5, and 10, were identified using PCR and agglutination assays. Animal challenge experiments demonstrated that all three strains could induce oviduct obstruction in 30-, 60-, and 90-day-old hens. Genomic sequencing analysis revealed 18 mutated virulence genes associated with diverse virulence determinants, including type IV secretion systems (T4SSs), hemolysin, yersiniabactin (Ybt), lipooligosaccharide (LOS), lipopolysaccharide (LPS), BrkA, capsule biosynthesis, flagella, caseinolytic protease C (ClpC), FeoAB, and Vi antigens, all of which have been established as critical factors in bacterial pathogenicity.ConclusionThe findings of this study confirm an association between R. anatipestifer infection and reduced egg production in hens, and provide a foundation for elucidating the specific roles of virulence genes in the altered pathogenicity of R. anatipestifer in chickens.